Diagnóstico de los emprendimientos en el sector agroproductivo del cacao del recinto 24 de mayo del cantón Buena Fe - Wong Cedeño, Roberto Samuel (2025)
This research on entrepreneurs in the cocoa agricultural production sector in the 24 de Mayo district of Cantón Buena Fe aims to identify actions needed to boost the growth and sustainability of these enterprises. The methodology used includes document analysis, surveys, and interviews to gather information on the challenges and opportunities faced by cocoa producers in the area. The main results highlight the lack of access to adequate technology, the need for technical training, the importance of product and market diversification, and promoting cooperation among sector stakeholders as key factors to improve productivity and farmers' quality of life. It is concluded that implementing training and technical assistance strategies, strengthening infrastructure for cocoa processing and storage, and promoting sustainable production practices are essential. The recommendations, it is suggested to continue the research, establish strategic alliances in the sector, develop study plans related to cocoa cultivation and agrochemical management of lands, and prioritize training for small and mediumsized producers. These actions have the potential to improve productivity, increase farmers' incomes, and contribute to the sustainable development of the cocoa region.